Aberrant Long Noncoding RNAs Expression Profiles Affect Cisplatin Resistance in Lung Adenocarcinoma. (27th November 2017) - Hu, Lijuan; Chen, Jian; Zhang, Fan; Wang, Junjun; Pan, Jingye; Chen, Jie; Wang, Yumin
Abstract : Background . Long noncoding RNAs (lncRNAs) have been shown to be involved in the mechanism of cisplatin resistance in lung adenocarcinoma (LAD). However, the roles of lncRNAs in cisplatin resistance in LAD are not well understood. Methods . We used a high-throughput microarray to compare the lncRNA and mRNA expression profiles in cisplatin resistance cell A549/DDP and cisplatin sensitive cell A549. Several candidate cisplatin resistance-associated lncRNAs were verified by real-time quantitative reverse transcription polymerase chain reaction (PCR) analysis. Results . We found that 1, 543 lncRNAs and 1, 713 mRNAs were differentially expressed in A549/DDP cell and A549 cell, hinting that many lncRNAs were irregular from cisplatin resistance in LAD. We also obtain the fact that 12 lncRNAs were aberrantly expressed in A549/DDP cell compared with A549 cell by quantitative PCR. Among these, UCA1 was the aberrantly expressed lncRNA and can significantly reduce the IC50 of cisplatin in A549/DDP cell after knockdown, while it can increase the IC50 of cisplatin after UCA1 was overexpressed in NCI-H1299. Conclusions . We obtained patterns of irregular lncRNAs and they may play a key role in cisplatin resistance of LAD.